Reductive activation of the prodrug 1,2-bis(methylsulfonyl)-1-(2-chloroethyl)-2-[[1-(4-nitrophenyl)ethoxy]carbonyl]hydrazine (KS119) selectively occurs in oxygen-deficient cells and overcomes O(6)-alkylguanine-DNA alkyltransferase mediated KS119 tumor cell resistance - Baumann, Raymond P. (2009)
1,2-Bis(methylsulfonyl)-1-(2-chloroethyl)-2-[[1-(4-nitrophenyl)ethoxy]carbonyl]hydrazine (KS119) is a prodrug of the 1,2-bis(sulfonyl)hydrazine class of antineoplastic agents designed to exploit the oxygen-deficient regions of cancerous tissue. Thus, under reductive conditions in hypoxic cells this agent decomposes to produce the reactive intermediate 1,2-bis(methylsulfonyl)-1-(2-chloroethyl)hydrazine (90CE), which in turn generates products that alkylate the O(6)-position of guanine in DNA. Comparison of the cytotoxicity of KS119 in cultured cells lacking O(6)-alkylguanine-DNA alkyltransferase (AGT) to an agent such as Onrigin™, which through base catalyzed activation produces the same critical DNA G-C cross-link lesions by the generation of 90CE, indicates that KS119 is substantially more potent than Onrigin™ under conditions of oxygen deficiency, despite being incompletely activated. In cell lines expressing relatively large amounts of AGT, the design of the prodrug KS119, which requires intracellular activation by reductase enzymes to produce a cytotoxic effect, results in an ability to overcome resistance derived from the expression of AGT. This appears to derive from the ability of a small portion of the chloroethylating species produced by the activation of KS119 to slip through the cellular protection afforded by AGT to generate the few DNA G-C cross-links that are required for tumor cell lethality. The findings also demonstrate that activation of KS119 under oxygen-deficient conditions is ubiquitous, occurring in all of the cell lines tested thus far, suggesting that the enzymes required for reductive activation of this agent are widely distributed in many different tumor types.